Analisis Kemampuan Berpikir Kreatif Matematis Siswa Kelas VIII MTs Nurus Salam Deli Tua Pada Materi Pola Bilangan - Ranti Amelia; Hizmi Wardani Anwar (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2022)
This study aims to analyze and describe students' mathematical creative thinking skills and to find out the causes of students' low mathematical creative thinking skills in number pattern material. This descriptive study uses qualitative methods that provide an overview of student's creative thinking skills in solving mathematical problems. The data collection technique used is a test technique using 20 questions of an early mathematical ability test, four questions of a mathematical creative thinking ability test, and interviews. The indicators of mathematical creative thinking skills are fluency, originality, flexibility, and elaboration. Data analysis found that subjects with high, medium, and low abilities could only meet two indicators: fluency and elaboration. Subjects with high abilities were categorized into the criteria for creative thinking skills with a percentage of 62.5%. Meanwhile, students with moderate abilities are categorized into the criteria for creative thinking skills with a percentage of 50%, and students with low abilities are categorized into the criteria for less creative thinking abilities with 25%.